Freedom of Speech in the Context of Constitutional Law: Maintaining the Balance Between Freedom and Public Order - Susianto; Nahuddin, Yusuf Eko; Nurita, Riski Febria (International Journal of Sustainable Law, 2025)
Freedom of speech is a fundamental human right in democratic systems, including in Indonesia, which is guaranteed by the 1945 Constitution of the Republic of Indonesia. However, despite being protected by the constitution, this freedom is not absolute and needs to be limited in certain cases to maintain public order, national security, and the rights of others. This study aims to analyze how freedom of speech is regulated in Indonesia's constitutional law, and how the state maintains the balance between individual freedom and public order. Using a normative research method, this study examines the legislation related to freedom of speech, such as the 1945 Constitution, the Electronic Information and Transactions Law (UU ITE), and relevant Constitutional Court decisions. Limitations on freedom of speech in Indonesia are regulated based on international legal principles that recognize freedom of expression, with the caveat that this right can be limited for the sake of public interest, morality, and national security. The findings of this study indicate that while freedom of speech is a crucial right in democracy, the state has the authority to limit this freedom under certain conditions. These limitations must be applied proportionally and in accordance with the principles of a democratic rule of law. The state plays a vital role in creating a balance between freedom of speech and public order, ensuring that this freedom can be maximized without undermining the social and political stability of the country.